The Effect of Sugarcane bagasse on The Performance of Coffee Waste Membrane for Peat Water Purification - Sudarmanto, Richard; Pratiwi, Indah; Hadi Arsalan, Adham; Imelda Margareta Br Sinurat, Weni; Sasmitha Sitompul, Aprina (Journal of Innovation Process and Environmental Technology, 2025)
This study investigates the potential of using sugarcane bagasse and coffee waste in membrane filtration for the purification of peat water. Peat water, known for its high organic content and challenging chemical properties, presents significant difficulties in traditional water treatment methods. Membrane technology has emerged as a promising solution, and this research aims to evaluate the effectiveness of membranes made from agricultural waste. Membranes were fabricated using different ratios of sugarcane bagasse and coffee waste, and their performance was tested based on parameters such as pH, turbidity, and Total Dissolved Solids (TDS). The results indicated that the 50:50 ratio of sugarcane bagasse to coffee waste provided the best outcomes in terms of pH neutralization and turbidity reduction, although the process still showed limitations in removing dissolved solids and addressing color and odor. This study demonstrates that while natural materials like sugarcane bagasse and coffee waste offer a sustainable alternative for water purification, further optimization and additional treatments are necessary for improving the removal of dissolved contaminants.